Management and outcomes of urethral stricture: single centre experience over 13 years - Akyuz, Mehmet; Ozsoy, Emrah; Tokuc, Emre; Artuk, Ilker; Kayar, Ridvan; Bastug, Yavuz; Öztürk, Metin İshak (Aktuelle Urologie, 2022)
Aim: To present a comprehensive summary of the diagnosis, treatment and follow-up process of patients who underwent open urethroplasty in our tertiary referral center for the treatment of urethral stricture in the last 13 years.Materials and methods: Two hundred and forty-five (245) patients who underwent open urethroplasty between January 2008 and June 2021 were retrospectively analysed. Detailed history, physical examination, uroflowmetry, retrograde urethrography and/or voiding cystourethrography and/or urethroscopy were used throughout the preoperative diagnosis process. While evaluating the postoperative patency rates, the absence of preoperative voiding symptoms after the operation and Qmax 15 ml/sec and above were taken into account.Results: Mean stricture length was 3.8 +/- 1.4 cm. Transurethral endoscopic interventions in 79 patients (32.2%), catheterisation in 55 patients (22.4%), trauma in 54 patients (22%), infection in 15 patients (6.2%), and idiopathology in 42 patients (17.2%) were the causes for the stricture. Buccal mucosal graft was used in 125 patients (51%), penile skin flap in 32 patients (13%), end-to-end anastomosis in 83 patients (33.8%) and Heineke-Mikulicz technique in 5 patients (2%). Mean follow-up period was 67.1 +/- 28.9 months. Success rates of patients were 84% (105) in buccal mucosal graft, 78.1% (25) in penile skin flap, 86.7% (72) with end-to-end anastomosis and 80% (4) with Heineke-Mikulicz technique.Conclusion: Among treatment options for urethral stricture, urethroplasty techniques is the most successful treatment. Consideration of the factors leading to the formation of the stricture, with the intraoperative findings and surgical experience will maximize the benefit the patient receives.
Keywords: Urethra; Stricture; Treatment; Urethroplasty